Taking the therapeutic community outside in the COVID-19 pandemic. Issue 2 (28th June 2021) - Jones, Merryn; Howe, Andrew John
Abstract : Purpose: The COVID-19 pandemic has affected psychotherapy practice. A common change is a move to online sessions over video calls. In their therapeutic community (TC) for those with personality disorders, the authors have used video calls but not all clients could work in this way. The authors decided to meet patients outside and walked with them while adhering to government guidelines. This study aims to present the authors' experience with one client who was interviewed afterwards about the experience. Design/methodology/approach: A total of 10 walking therapy sessions of 60-min duration were conducted with the patient. After the sessions, both the patient and therapist were interviewed about their experience. The resulting interviews with both patient and therapist were thematically analysed independently by both authors. Findings: There were common themes to both the client and therapist's account following thematic analysis. These were: modelling and normalising in the real world, replacing what COVID-19 had taken away from the TC experience, changes at home, therapist disclosure, outcomes and good endings and being outside of the clinical environment. Research limitations/implications: The authors have presented a single case of the patient and therapist experience of outdoor therapy sessions in a TC context response to the COVID-19 pandemic. The findings are not generalisable and can only provide a suggestion at the positive potential for working in this way. The authors hope that the positive effects of outdoor therapy noted here may inspire other clinicians to consider similar novel approaches in their work. Originality/value: This study describes a novel way that a TC has adapted to the COVID-19 pandemic.